Association between Inflammatory Factors in the Aqueous Humor and Hyperreflective Foci in Patients with Intractable Macular Edema Treated with Antivascular Endothelial Growth Factor. (8th June 2021) - Li, Min; Li, Jing; Chen, Kaichuan; Wang, Jia; Sheng, Minjie; Li, Bing
Abstract : Background . To evaluate the correlations between the inflammatory factors in the aqueous humor and hyperreflective foci (HRF) in patients with intractable macular edema treated with antivascular endothelial growth factor (anti-VEGF). Methods . This study included 17 patients with intractable macular edema (ME) treated with anti-VEGF agents. Inflammatory factors in the aqueous humor were measured by the Cytometric Beads Array before injection, and the numbers of HRF pre- and post-anti-VEGF treatment were counted from four different directions (90 degrees, 45 degrees, 180 degrees, and 135 degrees) in the SD-OCT images, respectively, before treatment and one month after treatment. The correlations between inflammatory factors and the numbers of HRF were assessed. Results . The numbers of HRF were reduced significantly after anti-VEGF treatment. The change in the HRFs at the 90-degree location was significantly positively correlated with IL-8 and VCAM-1. The change of all HRFs was significantly positively correlated with IL-8. The HRFs before the treatment also had a positive correlation with IL-8 and VCAM-1. Conclusion . After anti-VEGF treatment, the numbers of HRF in intractable ME declined greatly. The higher the levels of IL-8 and VCAM-1 before treatment, the more significant the reduction of HRF after anti-VEGF treatment, which indicated that HRF could be an effective noninvasive imaging indicator for evaluating the effect of anti-VEGF on intractable macular edema. The OCT images at the 90-degree location could better show the inflammatory reaction of patients and also had better clinical significance for the prognosis evaluation of ME associated with inflammation.